2012
DOI: 10.1108/03074801211218561
|View full text |Cite
|
Sign up to set email alerts
|

Web 2.0 in library and information science education: the Greek case

Abstract: Δημοσιεύσεις Μελών—ΣΔΟ – Βιβλιοθηκονομίας και Συστημάτων Πληροφόρησης, 2012The purpose of this paper is to find out what the Greek library and information science (LIS) students want from their studies concerning the use of Web 2.0 in education. Based on the results of this study, this paper will seek to identify problems and propose solutions that will tackle students' needs and improve the quality of their studies.A web‐based questionnaire was distributed to students of the Library Science and Information Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Of the various web-based applications studied (Kroski, 2008;Harinarayana and Raju, 2010;Si et al, 2011;Garoufallou and Charitopoulou, 2012;Mahmood and Richardson, 2013), web browser extensions are among the least examined areas. Research on the applications of web browser extensions in libraries carried out so far mostly concentrated on library toolbars (Jones, 2008;Wilson, 2009;Si et al, 2012), plug-ins and add-ons, and to basically guide librarians in the implementation of specific types of applications (Brown, 2007;Huynh et al, 2007;Wolf, 2008;Walker-Headon, 2010).…”
Section: Literature Review 21 General Studiesmentioning
confidence: 99%
“…Of the various web-based applications studied (Kroski, 2008;Harinarayana and Raju, 2010;Si et al, 2011;Garoufallou and Charitopoulou, 2012;Mahmood and Richardson, 2013), web browser extensions are among the least examined areas. Research on the applications of web browser extensions in libraries carried out so far mostly concentrated on library toolbars (Jones, 2008;Wilson, 2009;Si et al, 2012), plug-ins and add-ons, and to basically guide librarians in the implementation of specific types of applications (Brown, 2007;Huynh et al, 2007;Wolf, 2008;Walker-Headon, 2010).…”
Section: Literature Review 21 General Studiesmentioning
confidence: 99%
“…Training programs could enable a librarian to cope with the Web 2.0 technologies. Garoufallou and Charitopoulou (2012), to find out what the Greek Library and Information Science students want from their studies concerning the use of Web 2.0 in education, carried out a research and finally, revealed that most of the students are aware of the majority of Web 2.0 tools. Thus, they are willing to attend training concerning Web 2.0 because they believe this will enrich their knowledge on the subject.…”
Section: Web 20 Adoptionmentioning
confidence: 99%
“…To provide research support to the scholarly community of its parent institute, a library adopts various online tools and guides the researchers to use those tools at different stages of their research pursuit. The rapid development of online technologies has encouraged libraries to switch over to innovative and quicker access to resources and facilities (Garoufallou and Charitopoulou, 2012;Mahmood and Richardson, 2013;Santosh, 2017). Research services of a library encompass offering various research tools and techniques to provide thorough support to research activities.…”
Section: Introductionmentioning
confidence: 99%